Research approaches on the application of medicinal plant extraction in inhibition of fungal towards the improvement of indoor air quality 2010-2020: a systematic review: article - Mokhtarul Kudus, Maizatul Raihanah (2021)
This review provides current information on the application of medicinal plant extraction in inhibition of fungal towards the improvement of indoor air quality 2010-2020 based on analysis of published studies. A systematic literature search of ResearchGate, ScienceDirect, PubMed, Google Scholar and Wiley Online Library from 2010 to 2020 was conducted based on PRISMA Guideline without excluded other relevant articles found during the search. A systematic review search on the topic was conducted using appropriate databases to identify potentially relevant citations. The findings of this review are to listed certain type of medicinal plant extractions against various pathogenic fungi and standardize the method of extraction use in medicinal plants extraction thus evaluate certain medical plant extraction has a potential to inhibit pathogenic fungi that will improve the indoor air quality thus will avoid health issues among community.